Reforma eleitoral: consequência da crise institucional brasileira - Resende, Bárbara Machado Cherulli Altimari (2018)
The primary function of the on-screen study is to evaluate the performance of political power understood as the cause of the existence of a state and consequently responsible for the main positive and negative effects that the components of this state may suffer. The scenario of institutional crisis in Brazilian society may turn out to be a result of resistance to the inherent and necessary changes in the cultural scene of national politics while it suffers the most diverse side effects of a power struggle and utopian autonomy of those who represent us. Aware of the perplexed system introduced, the content of the political reform currently discussed can be seen as an advance in the sense of restraining - or at least attempting - nebulous articulations that are of no benefit to the well-being of the Brazilian citizen, while, on the other hand, absolute frankness, its real intentions, and may be an instrument of maneuver, which will enable a greater concentration of political power, rooted in economic power, expressly disregarding the democratic regime already so mitigated in our present society. Believing that the political scenario has undergone considerable changes and that the immediate effects will be drastically felt by the society that submits to it is concluded by the study on screen that will be directed in the intention to evaluate the content approved for electoral reform considering all time the evaluation of some basic and indispensable concepts that revolve around the theme addressed, stating when possible the possible positive and negative effects generated by the imposition of a new systematic policy, always seeking the preservation of social welfare and maintenance of effective representativeness of the minority, protecting the democratic State of law.